Aryl-, Akynyl-, and Alkenylbenziodoxoles: Synthesis and Synthetic Applications; Molecules; Vol. 28, iss. 5 - Mironova I. A. Irina Andreevna; Noskov D. M. Dmitry Mikhaylovich; Yoshimura A. Akira; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Zhdankin V. V. Viktor Vladimirovich (2023, 2023)
Title screen